Transnationality in Translation (translation. a transdisciplinary journal, 2022)
At the outset, let me note the increasing significance of the problematic of "bordering" in knowledge production today. 2 This problematic must be marked specifically as one not of "border" but of "bordering" because what is at issue is a great deal more than the old problem of boundary, discrimination, and classification. At the same time that it recognizes the presence of borders, discriminatory regimes, and the paradigms of classification, this problematic sheds light on the processes of drawing a border, of instituting the terms of distinction in discrimination, and of inscribing a continuous space of the social against which a divide isintroduced. The analytic of bordering requires us to examine simultaneously both the presence of border and its drawing or inscription.